IMPLEMENTASI MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Suprasetyo, Yusuf Nomi; Sujiarto, Heru Sujiarto; Sulastri, Yayu Laila (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
This research is motivated by the low critical thinking skills of students in mathematics learning in Class XI of SMK Putra Bahari. The aim of this study is to determine the students' critical thinking skills using the inquiry  learning model. The research method used is Classroom Action Research (CAR) conducted over 3 cycles, following the steps of planning, action, observation, and reflection. The data collected include qualitative data from teacher observations and student observations, as well as quantitative data from learning outcomes obtained through formative tests. The data obtained were analyzed using percentages. The results of the data analysis conclude that there is an improvement in students' critical thinking skills using the inquiry  learning model.   Keywords: Critical Thingking Skills, Inquiry -Based Learning